2000
DOI: 10.1046/j.1472-765x.2000.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Indigo production by naphthalene-degrading bacteria

Abstract: A I N . 2000. A wild-type naphthalene-degrading strain Pseudomonas putida RKJ1 and two recombinant strains each of Ps. putida and Escherichia coli carrying the genes for naphthalene degradation on a recombinant plasmid pRKJ3, produced indigo and indirubin pigments from indole. Naphthalene, salicylate and IPTG induced cells of naphthalene-degrading recombinant bacteria produced up to two times higher indigo compared with the uninduced cells. The maximum rates of indigo formation by Ps. putida RKJ1, Ps. putida R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 17 publications
(28 reference statements)
2
25
0
Order By: Relevance
“…peaks at m/z 148 and 263 with retention times of 3.5 and 9.9 min were observed (Supplementary information), which exactly matched the fragmentation pattern of commercial isatin and indigo standards, respectively. Compared with fragmentation pattern and UV-visible spectra in previous reports, it further confirmed that these two compounds were isatin (3.5 min) and indigo (9.9 min) (O'Connor et al 1997;Bhushan et al 2000;Meyer et al 2002).…”
Section: Mechanisms Of Indigo Biosynthesis By Comamonas Sp Mqsupporting
confidence: 72%
See 1 more Smart Citation
“…peaks at m/z 148 and 263 with retention times of 3.5 and 9.9 min were observed (Supplementary information), which exactly matched the fragmentation pattern of commercial isatin and indigo standards, respectively. Compared with fragmentation pattern and UV-visible spectra in previous reports, it further confirmed that these two compounds were isatin (3.5 min) and indigo (9.9 min) (O'Connor et al 1997;Bhushan et al 2000;Meyer et al 2002).…”
Section: Mechanisms Of Indigo Biosynthesis By Comamonas Sp Mqsupporting
confidence: 72%
“…and Acinetobacter spp. (O'Connor and Hartmans 1998;Bhushan et al 2000;Qu et al 2010). However, indigo biosynthesis from indole by Comamonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalene dioxygenase was soon found not to be the only enzyme capable of indole oxidation: several other oxygenases that accept indole as a substrate have been identified (5)(6)(7)(8)(9)(10). These are either enzymes similar to naphthalene dioxygenase that activate oxygen with iron centers or members of the cytochrome P450 family (6,11).…”
mentioning
confidence: 99%
“…HOB1 was found to be 77.8 nmol min −1 mg dry biomass −1 . This rate of indigo formation is 50-100 times higher as compared to the indigo formation rates (0.60, 0.80, 1.2, and 1.5 nmol min −1 mg dry biomass −1 ) reported by Bhushan et al [19] under different inducing conditions with wild-type Pseudomonas putida strain as well as [16,20] have reported indigo formation rate of 8.3 and 12 nmol min −1 mg dry biomass −1 , respectively, which is again much less than indigo formation rate by Pseudomonas sp. HOB1.…”
Section: Kinetics Of Indigo Formationmentioning
confidence: 47%